Characterization of Human Nails Samples Using FTIR (Fourier Transform Infrared) Through Chemometric Methods PCA and Clustering - Juwita, Shinta Shaleha; Trisnawati, Ni Luh Putu; Suyanto, Hery (BULETIN FISIKA; Vol 22 No 2 (2021): BULETIN FISIKA August Edition, 2021)
Research has been carried out on the characterization of human nail samples by FTIR (Fourier Transform Infrared) using Chemometric PCA and Clustering methods. The sample used was left middle fingernail (TTK) from three people from one family (SKR) and two people who were not family (BKR ). The test was carried out on TTK nail samples with a mass ratio of TTK nails with KBr 3:1. The results characterization by FTIR showed the presence of functional group O-H, C-H, C=O, N-H, C-N, P=O, C-O-C, nitrate, and nitrite in the TTK nail samples. The results of the analysis using the Chemometric PCA and Clustering methods showed that the TTK nail samples showed similarity in one family. This is based on the similarity of the types of molecules and their absorbance values. In addition, based on the results of PCA loading analysis, the wavenumber identity of the TTK nail samples were found in the range 1597-1479 cm -1 .